Deep learning strategies for active secondary metabolites biosynthesis from fungi: Harnessing artificial manipulation and application. (November 2021) - Mohamed, Hassan; Hassane, Abdallah; Atta, Omar; Song, Yuanda
Abstract: Microorganisms mainly fungi considered the most natural inhabitants of diverse environments exhibit enormous interactions capabilities to produce active molecules. However, these substances are typically produced only in limited amounts by their native hosts. The native organisms may also be difficult to cultivate and genetically engineer, and some can produce undesirable toxic bio-products. The biologically active secondary metabolites from endophytic fungi showed several kinds of bioactivities, comprising antimicrobial, anti-tumor, anti-inflammatory, immunomodulatory and anti-diabetes, developing functional constipation activities. Particularly, the novel biotechnological procedures including co-cultivation and various fermentation strategies to enhance fungal biomass and subsequently increasing valuable active products with maximum yields, have been paid more and more attention by scientists and researchers, but most endophytic fungi appear to be uncultivable, and for those that can be cultivated, their metabolic potential lies largely invisible through regulatory silencing of biosynthetic genes for secondary metabolites production. This review introduced the biologically active metabolites and their main classes from fungi through artificial manipulation methods, effects and substrates, in recent years, and then the relationships between active molecules and their bio activity effects were also discussed. Highlights: Endophytic fungi as a promising candidate for biologically active compounds. Various fermentation strategies were reviewed to increase active metabolites. Main classes of active metabolites were introduced and their application. Several biological applications were included with their active metabolites.